An Analysis of "A orfa de San Lourenzo" by Rogelio Civeira - Eirín García, Leticia (Madrygal. Revista de Estudios Gallegos, 2015)
In this paper we analyze the play A orfa de San Lourenzo. Drama n-un auto i-en verso, written by Rogelio Civeira, with the aim of demonstrating its presence in the so-called ‘regionalist theater’. The piece was awarded at the “Galician literary contest” held in Pontevedra in 1886, and published in the same year, together with the other awardwinning works, in a set volume.